Analisis Stilistika Mantra Pengobatan di Kelurahan Ukui Kecamatan Ukui Kabupaten Pelalawan - Yolanda, Yolanda (UIR PRESS, 2022)
This research is motivated by the Malay mantra in Ukui Village which contains elements of the beauty of language, these elements are part of the stylistic study. These elements consist of aspects of sound and figurative language/figurative language. The problems in this study are (1) How is the stylistic analysis of the sound aspects contained in the treatment spell in Ukui Village, Ukui District, Pelalawan Regency? (2) How is the stylistic analysis of the figurative/figurative language contained in the healing spell in Ukui Village, Ukui District, Pelalawan Regency? The purpose of this study is to describe, analyze and interpret aspects of sound in healing spells in the community in Ukui Village, Ukui Subdistrict, Pelalawan Regency and to describe, analyze, and interpret figurative language/figurative language in healing spells in the community in Ukui Village, Ukui Subdistrict, Pelalawan Regency. The theory used in this study is the theory of Nurgiyantoro (2014), Pradopo (2012), Pradopo (2020) and other supporting theories. The data of this research is in the form of sound aspect which consists of rhyme, rhythm, tone and atmosphere and figurative language which consists of comparative figure of speech (simile, metaphor, personification, allegory) and linkage figure of speech (metonymy and synecdoche). This study uses a descriptive analysis method with the type of field research and uses a qualitative approach. Data collection techniques with interview techniques, documentation and recording. The results of this study can be concluded that there are stylistic elements in the treatment mantra in Ukui Village, namely the sound aspect of poetry which amounts to 217 words, rhythm which amounts to 174 words, tone and atmosphere which amounts to 151 words and figurative language/figurative language in personification figure of speech which amounts to 4 data and figure of speech synecdochi which amounted to 1 data. An example of the aspect of the rhyme sound at the end with an abab pattern in a stomachache medicine spell and an example of a synecdoki figure of speech figurative language on a sore throat medicine spell.